Renewable Energy Policy in Indonesia: The Qur’anic Scientific Signals in Islamic Economics Perspective - Jaelani, Aan; Firdaus, Slamet; Jumena, Juju (International Journal of Energy Economics and Policy, 2017)
This study confirms that renewable energy sources become the solution for energy development in Indonesia due to the increasingly depleted use of fossil-based energy, due to an increase in the population that increases energy consumption and waste in fuel consumption. The Qur’an has provided simple concepts and illustrations about renewable energy sources that can be utilized by humans, energy conservation, and energy enrichment. With the codification and content analysis approach to energy policy in Indonesia and energy themes in the Qur’an, this paper asserts that the Government of Indonesia’s renewable energy policy focuses on providing and developing renewable energy as part of sustainable development. This renewable energy policy can be proven scientifically with the implementation of scientific Qur’anic terms about renewable energy sources such as water, geothermal, ocean, vegetation, and wind. The policy on energy conservation through energy saving becomes a religious obligation for every person, institution, and government because to meet the needs of consumers, maintain the survival of the community, and preserve the environment. Keywords: renewable energy, energy conservation, energy efficiency, energy economy JEL Classifications: Q28, Q48, Q58